Observational investigation of the possible correlation between medium-scale TIDs and mid-latitude spread F. Issue 3 (1st August 2016) - Yu, Shimei; Xiao, Zuo; Aa, Ercha; Hao, Yongqiang; Zhang, Donghe
Highlights: MSTIDs are extracted from GPS TEC and the morphological features are presented. MSTIDs and MSF shows consistent morphological features and longitudinal dependence. Regional GWs may trigger local MSF and produce the longitudinal differences. Abstract: Global navigation satellite system (GNSS) receivers at two stations, CHAN (43.83°N, 125.27°E) and URUM (43.70°N, 87.60°E) in China, are used to retrieve the total electron content (TEC) from 2001 to 2012, and detect medium-scale traveling ionospheric disturbances (MSTIDs) above the two stations. At either station, MSTIDs occurrence is found to depend on season and solar cycle, that is, lower during equinoctial seasons and low solar activity, in accordance with the general morphological features of mid-latitude spread F (MSF). More interestingly, a significant longitudinal difference exists between the two stations that, both MSTIDs and MSF are more prevalent at CHAN than at URUM over the 12 years. These results imply a strong connection between MSTIDs and MSF, and provide new observational evidences that gravity waves (GWs), manifested in MSTIDs here, might play an important role in triggering MSF in the overhead ionosphere. Since GWs at mid-latitude mostly originate in the lower atmosphere, we infer that the atmospheric background at CHAN is more favorable for generating GWs. This is probably true considering very different surface meteorological conditions for the two stations over such a large longitudinal span (∼38°). CHAN station is near the coast of western Pacific Ocean and URUM station is in the very center of the Europe–Asia continent, and they are in different climate zones. We therefore suggest that the surface meteorological condition is one of the significant factors to be considered in explaining and modeling MSF formation and variations.